Anesthetic pain management in Siriraj Hospital: A retrospective review - Pongparadee Chaudakshetrin (2018)
Neural blockade has been used as the single method to anesthetize a part of the body or used in combination with general anesthesia to lessen perioperative pain. Currently, nerve blocks are used for diagnostic, prognostic, therapeutic and prophylactic proposes for management of chronic, acute and cancer pain in a Pain Clinic. Reviewing the records of the 3,349 patients at Siriraj Pain Clinic, we found 2,662 and 687 cases had chronic and acute pain problems respectively, and only 646 patients were treated with anesthetic interventions during 1990 to 1998. They consisted of 317 male and 329 female. The techniques included stellate ganglion block, paravertebral nerve block, celiac plexus block, hypogastric plexus block, mesenteric plexus block, sacral nerve block, epidural steroid, lumbar sympathectomy, first and second thoracic sympatholysis, facet joints injection, sacroiliac joint injection, intravenous regional block with guanethidine or ketanserin, continuous opioid infusion, intravenous lidocaine infusion, and a phentolamine test. The common problems of pain included brachial plexus injury, chronic spinal pain, herpetic neuralgia, ischemic pain, central post-stroke pain, and causalgia. This retrospective review showed that 38 per cent of them reported 50 per cent pain relief with temporary effect. 34 per cent experienced good and satisfactory pain relief while 9 per cent reported excellent pain relief. 17 per cent did not gain benefit from any technique of pain relief and about 2 per cent could not be evaluated due to they did not return for follow-up. One serious complication after thoracic sympatholysis was brachial plexus injury. The neural blockade is proven to be one of the useful adjunct in the management of chronic pain but the selection of the technique is subjected to its critical appraisal.